Crisis logistics: The role of disaster relief in supply chain risk management for emergency response - Abu-Alhaija, Ahmad Saifalddin; Allahham, Mahmoud; Alsawaha, Ahood; Almagharbeh, Bashar khaled; Alsharif, Nuha Abdulrahaman (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate the obstacles regarding Supply Chain Risk Management (SCRM), addressing such timely and pertinent issues as emergency response and how disaster relief works to moderate these effects. The research shifts the focus toward complex contexts that are heavily disrupted and uncertain, particularly in natural disaster and humanitarian crisis settings. The study assesses the intricate coupling in supply chain networks under distinctive disaster-impacted institutional settings through extensive fieldwork and sophisticated analytical methods. Data was collected through a field survey of 150 logistics and disaster response employees from diverse non-governmental and relief organizations. The findings demonstrate that SCRM practices help boost readiness to cope with emergencies; nevertheless, many logistical and infrastructural limitations still prevent seamless case handling. Although disaster relief constitutes the most considerable mediating effort to alleviate these barriers, significant gaps exist due to a lack of coordination and overall pragmatism towards the equal distribution of resources peripherally involved within such initiatives. This study can benefit supply chain managers and relief organizations by providing valuable policy insights and guidance on operational issues that are important in dealing with risk and response to emergencies, such as resource allocation, collaboration between different sectors, and preemptive planning. This research offers unique insights into the role of SCRM in high-risk settings by illustrating the importance of disaster relief in performing necessary bridging roles that connect operations and providing a novel perspective on preparedness practices through the lens of supply chain management.